(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The proposed system in this paper describes the design and implementation of a Wireless Sensor Network (WSN) based on ZigBee technology to monitor the history and current temperature information of remote locations. The system is an electronic embedded system that contains: Base Station with coordinator ZigBee, End nodes with router ZigBee, and host computer as a data base (DB) server. The base station is responsible for data collecting, a display for end node sensor readings, and TCP/IP communication with the host computer. End nodes are directly connected with sensors and transmitting the readings of these sensors to the base station. The host computer is responsible for building a data base from end nodes sensor readings. The Microcontroller Units (MCUs) from Peripheral Interface Controller (PIC) family have been used and the firmware has been developed using C language with MikroC Pro which is a full-featured ANSI C Compiler for Microchip PIC MCU as a development environment.